2015
DOI: 10.1128/jb.02198-14
|View full text |Cite
|
Sign up to set email alerts
|

The Bacteroides thetaiotaomicron Protein Bacteroides Host Factor A Participates in Integration of the Integrative Conjugative Element CTnDOT into the Chromosome

Abstract: CTnDOT is a conjugative transposon found in Bacteroides species. It encodes multiple antibiotic resistances and is stimulated to transfer by exposure to tetracycline. CTnDOT integration into the host chromosome requires IntDOT and a previously unknown host factor. We have identified a protein, designated BHFa (Bacteroides host factor A), that participates in integrative recombination. BHFa is the first host factor identified for a site-specific recombination reaction in the CTnDOT family of integrative and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“… 2000 , 2001 ; Keeton and Gardner 2012 ; Keeton et al. 2013a , Ringwald and Gardner 2015 ). Xis2c and Xis2d are essential for the excision of CTn DOT and bind to attL and attR (Hopp, Gardner and Salyers 2015 ).…”
Section: Experimental Model Ices: Mechanisms and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“… 2000 , 2001 ; Keeton and Gardner 2012 ; Keeton et al. 2013a , Ringwald and Gardner 2015 ). Xis2c and Xis2d are essential for the excision of CTn DOT and bind to attL and attR (Hopp, Gardner and Salyers 2015 ).…”
Section: Experimental Model Ices: Mechanisms and Regulationmentioning
confidence: 99%
“…To promote site-specific insertion, it is thought that IntDOT assembles at attDOT along with the host factor BHFa, to form the integrative intasome nucleoprotein complex (Ringwald and Gardner 2015 ). This integrative intasome differs from it excisive counterpart by the absence of Xis2c, Xis2d and Exc.…”
Section: Experimental Model Ices: Mechanisms and Regulationmentioning
confidence: 99%
“…Previous work has shown that the Bacteroides host factor BHFa binds and bends DNA (21). It also forms a complex with the wild type IntDOT protein.…”
Section: 3 Resultsmentioning
confidence: 99%
“…5A). The H3 site overlaps with the entire L1 arm-type site, but only 6 of the previously BHFa protected 37 bases were changed in the L1 mutant (L1 Mut ) arm-type HJ intermediate (22). It may be that nonspecific binding of BHFa to the HJ intermediates is sufficient for resolution.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Of the sites, BHFa has the highest affinity for the H2 site, less affinity for the paired H3-H4 sites, and the lowest affinity for the H1 site (22).…”
mentioning
confidence: 99%